Quantitative Analysis for the Reconstruction of Porous Media Using Multiple-Point Statistics - Qing Xie; Jianping Xu; Yuanda Yuan; Cong Niu (Geofluids, 2020)
The pore structure reconstruction of the porous media is of great importance to the research of mechanisms of fluid flow in porous media. To capture the large-scale patterns in the pore space, the multiple-point statistical technique is generally adopted for porous media reconstruction. Commonly, two different schemes, i.e., the single-grid scheme and the multiple-grid scheme, can be applied for simulation realization. The selection between this two schemes and a proper data template size have thus become a new research issue, and the performance of the characteristic reproduction of the training image using this two schemes must be quantified. In this paper, a series of multiple-point statistics simulation basing on a 2D micro-CT sandstone image are proceeded using both single- and multiple-grid schemes, and different data templates are adapted for porous media reconstruction. Further, to quantify the impact of the computational schemes and setting of the data template to the simulation realizations, a number of measurements considering the pore diameter, porosity, connectivity, and permeability are implemented to fully analyze the results obtained. Results show that by using the single-point statistical method, a large template is necessary to reproduce large-scale structures. The multiple-grid template method may bring great benefits to simulation efficiency over the simple data template method, as well as the recovery of the pore long-range geometric features and seepage characteristics. With the extension of the template for the multiple-grid scheme, the simulation results show lack of variations to some extent.